Предмет: Алгебра,
автор: vladasol
упростить выражение
12a3b2+6a2
18a4-3a2
Ответы
Автор ответа:
0
(12а³в²+6а²) (18а⁴ -3а²) = 6а² ( 2ав+1) 3а² ( 6а²-1) = 2(2ав+1) (6а²-1)
Автор ответа:
0
Спасибо, но некоторые элементы "потерялись" (12а³в²+6а²) (18а⁴ -3а²) = 6а² ( 2ав2+1) 3а² ( 6а²-1) = 2(2ав2+1) (6а²-1)
Автор ответа:
0
извиняюсь, уже исправляюсь!!!!!!!!!
Похожие вопросы
Предмет: Алгебра,
автор: dudhej
Предмет: Русский язык,
автор: dimaglobalik
Предмет: Алгебра,
автор: gornak2142
Предмет: География,
автор: Ксюшкааа2001